2003
DOI: 10.1207/s15327752jpa8102_07
|View full text |Cite
|
Sign up to set email alerts
|

The Sexual Sensation Seeking Scale: Reliablity and Validity Within a Heterosexual College Student Sample

Abstract: The Sexual Sensation Seeking Scale (SSSS; Kalichman & Rompa, 1995) is a measure of the propensity to seek out novel or risky sexual stimulation. This measure has been consistently related to HIV-risk behavior in several different samples of gay men and with behavioral correlates of sexual permissiveness in college students. Five hundred twenty-eight college students completed the SSSS and several other sexuality and personality measures. The results reveal significant gender differences on the SSSS and similar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
59
3
5

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(78 citation statements)
references
References 27 publications
11
59
3
5
Order By: Relevance
“…The Sexual Sensation Seeking Scale correlated positively with SE and all of its lowerorder factors, and showed weak, negative correlations with SI and its factors. This was consistent with research by Gaither and Sellbom (2003), who reported positive correlations between scores on the SSS and propensity for sexual excitation assessed using the SIS/SES.…”
Section: Validitysupporting
confidence: 91%
See 2 more Smart Citations
“…The Sexual Sensation Seeking Scale correlated positively with SE and all of its lowerorder factors, and showed weak, negative correlations with SI and its factors. This was consistent with research by Gaither and Sellbom (2003), who reported positive correlations between scores on the SSS and propensity for sexual excitation assessed using the SIS/SES.…”
Section: Validitysupporting
confidence: 91%
“…High scores on this measure have been shown to relate to sexual risk taking in a number of studies and to sexual excitation proneness as measured by the SIS/SES. The SSS has been found to show good reliability and construct validity (Gaither & Sellbom, 2003). Previous research using the SIS/SES in men (Gaither & Sellbom, 2003) had reported positive correlations between SSS scores and sexual excitation proneness, significant negative correlations with SIS2 (threat of performance consequences), and weak, positive correlations with SIS1 (threat of performance failure).…”
Section: Sexual Excitation/sexual Inhibition Inventory For Women (Sesmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior cross sectional studies, mostly with sexual minorities who are white males have indicated that SSS is associated with risky sex behaviors (Chng & Geliga-Vargas, 2000;Crawford et al, 2003;Dolezal et al, 1997;Kalichman, Heckman, & Kelly, 1996;Kalichman, Weinhart, & DiFonzo, 2002;McCoul & Haslam, 2001). Additionally, a handful of studies which included mostly mixed female samples have noted similar findings between SSS and risky sexual behaviors (Gaither & Sellbom, 2003;Hendershot, Stoner, George, & Norris, 2007;Jones, 2004;Stanton et al, 2001). These prior studies reported SSS means that ranged from 13.3 to 22.1 (Gaither & Sellbom, 2003;Jones, 2004;Stanton et al, 2001), which was inclusive of the mean (17.5) reported in this study.…”
Section: Resultsmentioning
confidence: 83%
“…The re are va ri o us to ols which ha ve be en de ve lo ped in dif fe rent are as of rep ro duc ti ve health. [8][9][10][11][12] Ho we ver the re are no to ols ava i lab le to mea su re yo ung pe op le's at ti tu des abo ut rep ro duc ti ve he alth in Tur kish with es tab lis hed va li dity and reli a bi lity.…”
mentioning
confidence: 99%